2003
DOI: 10.1183/09031936.03.00077702
|View full text |Cite
|
Sign up to set email alerts
|

COPD: problems in diagnosis and measurement

Abstract: Chronic obstructive pulmonary disease (COPD) is the most rapidly rising cause of death in individualsw65 yrs of age, the most rapidly growing segment of the USA population.Advancing the clinical research agenda for COPD entails careful consideration of several issues and problems: defining COPD, reliance on physiological testing, outcome measurements and comorbidities.In addition, issues pertaining to the recent dramatic increase in chronic obstructive pulmonary disease mortality in females, smoking susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 84 publications
2
16
0
3
Order By: Relevance
“…One of the difficulties of conducting clinical outcomes research in COPD is the high prevalence of comorbid conditions, especially those that are also caused by cigarette smoking (5). Persons with chronic airflow obstruction are known to have a substantially increased risk of coronary artery disease and sudden cardiac death (6 -10), and the degree of airflow obstruction is highly correlated with systemic inflammatory markers that are associated with coronary artery disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…One of the difficulties of conducting clinical outcomes research in COPD is the high prevalence of comorbid conditions, especially those that are also caused by cigarette smoking (5). Persons with chronic airflow obstruction are known to have a substantially increased risk of coronary artery disease and sudden cardiac death (6 -10), and the degree of airflow obstruction is highly correlated with systemic inflammatory markers that are associated with coronary artery disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that COPD is the most rapidly increasing cause of death in individuals older than 65 years of age, which represents the most rapidly growing segment of the population in developed countries. Disability from COPD is expected to rise by 2020 with aging of the population and the increase in disease prevalence (Weiss et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…'Never-smokers' can also contract COPD but this is restricted to a prevalence of about 4-5% of patients reporting physician-diagnosed COPD. 24 Grounded theory requires continuous theoretical sampling to direct further data collection. Given the limited number of possible patients, sampling was mainly purposeful and intended to describe the research area.…”
mentioning
confidence: 99%